An Investigation into Women's Experiences of the Free Contraception Scheme: Research Project Report. - Flynn, Susan (My University, 2026)
Access to contraception is a fundamental component of reproductive health and gender equality. In Ireland, despite significant progress in expanding access to free contraception, marginalised groups may face disproportionate barriers. This research sought to understand marginalised groups’ awareness and knowledge of the Free Contraception Scheme (FCS) and their experiences of accessing contraception more broadly. This included disabled women, those from the Traveller community, migrant women and LGBTIQ+ people who require contraception. The research highlights key challenges, incorporates testimonies from women, based on their lived experience, and provides targeted recommendations to ensure equitable access to contraception for all women in the Republic of Ireland. Prior to commencing the empirical research for this study, a narrative literature review was completed to establish the background and context for the research. For the study overall, the principal research question was: What awareness and experiences do contraception users from marginalised communities have of the Free Contraception Scheme? After the literature review, we conducted the research using a survey and focus groups. A survey questionnaire was distributed to women aged 18-35 years to gather preliminary data on their experiences of the FCS to date. This was statistically analysed using Qualtrics software. Additionally, four focus groups were conducted to gather marginalised women’s views and experiences with respect to the FCS. Focus group discussions were transcribed and thematically analysed.
PUBLISHED